The Prognostic Value of Neutrophil-to-Lymphocyte Ratio and Lymphocyte-to-Monocyte Ratio in Patients with Hepatocellular Carcinoma Receiving HAIC-Based Conversion Hepatectomy: A Dual-Center Retrospective Cohort Study - Li D; Fan Y; He B; Tang Y; Deng G; Guo R; Deng M; Tang D (Journal of Inflammation Research, 2025)
Dong Li,1,* Youwen Fan,1,* Benyi He,2,3 Yajun Tang,1 Gang Deng,1 Rongping Guo,2,3 Min Deng,1 Di Tang1 1Department of General Surgery, The Seventh Affiliated Hospital, Sun Yat-Sen University, Shenzhen, People’s Republic of China; 2Department of Liver Surgery, Sun Yat-sen University Cancer Center, Guangzhou, People’s Republic of China; 3State Key Laboratory of Oncology in South China, Guangdong Provincial Clinical Research Center for Cancer, Collaborative Innovation Center for Cancer Medicine, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Di Tang, Department of General Surgery, The Seventh Affiliated Hospital, Sun Yat-sen University, 628 Zhenyuan Road, Shenzhen, People’s Republic of China, Email tangdi@mail.sysu.edu.cn Min Deng, Department of General Surgery, The Seventh Affiliated Hospital, Sun Yat-sen University, 628 Zhenyuan Road, Shenzhen, People’s Republic of China, Email dengmin@sysush.comBackground: Clinical tools for predicting prognosis are limited for patients with hepatocellular carcinoma (HCC) undergoing hepatic arterial infusion chemotherapy (HAIC)-based hepatectomy. This study evaluated the prognostic significance of neutrophil-to-lymphocyte ratio (NLR) and lymphocyte-to-monocyte ratio (LMR) in patients with HCC who received HAIC-based hepatectomy.Methods: This dual-center retrospective study included 390 patients who received HAIC-based conversion resection to investigate the relationship of NLR and LMR with survival outcomes, adverse events, and risk factors.Results: A total of 390 patients with HCC who received HAIC-based conversion liver resection were included. Patients with NLR ≥ 5 exhibited a significantly shorter overall survival (OS) and recurrence-free survival (RFS) compared to those with NLR < 5 (P = 0.0181 and P = 0.0164, respectively). Patients with LMR ≥ 3 exhibited favorable OS and RFS rates compared to those with LMR < 3 (P = 0.0195 and P = 0.0225, respectively). Similar results were observed in patients who achieved an objective response. NLR ≥ 5 and LMR < 3 were significantly associated with decreased OS and RFS compared to NLR < 5 and LMR ≥ 3 (P = 0.0131, P = 0.0104, P = 0.0055, and P = 0.0329, respectively).Conclusion: NLR and LMR have an effective predictive capability in prognosis for patients with HCC who received HAIC-based conversion surgery. These findings may help surgeons and patients make decisions regarding HAIC-based conversion hepatectomy.Plain Language Summary: Patients with NLR ≥ 5 and LMR < 3 exhibited a significantly shorter OS and RFS than those with NLR < 5 and LMR ≥ 3. NLR≥ 5 and LMR< 3 were significantly associated with decreased OS and RFS compared to NLR < 5 and LMR ≥ 3 for patients who achieved an objective response. Our findings may be useful in guiding surgeons and patients in decision-making regarding HAIC-based conversion hepatectomy.Keywords: hepatic arterial infusion chemotherapy, conversion, hepatocellular carcinoma, neutrophil-to-lymphocyte ratio, lymphocyte-to-monocyte ratio